(untitled) (Damu Journal of Sport Sciences, 2025)
This study aimed to investigate the impact of single-stroke exercises on improving unilateral arm strength and the performance of female national team kayakers in the 200-meter event. An experimental approach was applied to a sample of 8 athletes, with a specialized 8-week training program (3 sessions per week). Pre- and post-tests included measurements of pulling/pushing strength for each arm and 200-meter sprint time. The results showed statistically significant differences (p < 0.05) between pre- and post-tests, with improvements in arm strength (right arm: 32 to 35 kg in pulling; left arm: 21 to 26 kg in pushing) and race time (51.4 to 49.4 seconds). The exercises also enhanced muscular balance and reduced injury risks. The study recommends integrating these exercises into training programs, emphasizing individualized plans and periodic assessments.